Practical Aspects of Declarative Languages 16th International Symposium, PADL 2014, San Diego, CA, USA, January 19-20, 2014, Proceedings - Flatt, Matthew; Guo, Hai-Feng (Programming and Software Engineering, 2014)
This book constitutes the refereed proceedings of the 16th International Symposium on Practical Aspects of Declarative Languages, PADL 2014, held in SanDiego, CA, USA, in January 2014, co-located with POPL 2014, the 41st Symposium on Principles of Programming Languages. The 15 revised papers presented were carefully reviewed and selected from 27 submissions. They cover a wide range of topics related to logic and functional programing, including language support for parallelism and GPUs, constructs and techniques for modularity and extensibility, and applications of declarative programming to document processing and DNA simulation.